Pengaruh ServicescapeTerhadap Kepuasan Tamu Evas Restoran di Hotel Grand Rocky Kota Bukittinggi - Yovi Dani Septian; Youmil Abrian; Arif Adrian (Departemen Pariwisata Universitas Negeri Padang, 2022)
This research begins with the phenomenon encountered related to complaints from guests and not maximising the servicescape that exists at Evas Restaurant Hotel Grand Rocky Bukittinggi. So that the author conducts this research with the aim of knowing the amount of influence of Servicescape on guest satisfaction at Evas Restaurant Hotel Grand Rocky Bukittinggi. type of research is descriptive quantitative by utilising the causal associative method which aims to determine how dominant the influence of Servicescape (X) on Guest Satisfaction (Y) Evas Restaurant Grand Rocky Hotel Bukittinggi. In the study, the sample was taken by utilising non-probability sampling techniques with a total of 100 people who had visited the Evas Restaurant at the Grand Rocky Hotel. Data was collected using a questionnaire that had been tested for validity and reliability. Data analysis techniques for hypothesis testing using linear regression analysis. After conducting the research process, the following research results were obtained: (1) servicescape is known to be included in the good category (84%), (2) Guest Satisfaction is known to be included in the good category (76%) (3) from testing the simple linear regression hypothesis, it is known that the amount of F count is 16.603 and the significant level is known to be 0.000 <0.05, the R square obtained a value of 0.145. This means that servicescape affects guest satisfaction by 14.5% and the rest in total 85.5% get influence from other factors. Furthermore, the calculated t value is 4.075 which is a significant level of 0.000 <0.05, with the t value obtained there is a significant relationship between the two variables.